Planar-Chiral P and N-bridged Diferrocenes - Philipp Honegger; Lukas Scheibelberger; Michael Widhalm (Molbank, 2020)
We describe the synthesis of planar-chiral diferrocene compounds 4, 7 and 12, intended as key precursors for a new family of asymmetric catalyst ligands with less complex structures than their popular equivalents. In contrast to conventional 1,2-disubstituted ferrocenes containing center-chiral and planar-chiral elements, these compounds are purely planar-chiral due to the absence of α-substiuted ethyl groups. The title compounds 4, 7 and 12 were obtained from known precursors in 87%, 59% and 60% yields, respectively.